Government and liberty - Rice, Arthur Daniel (My University, 1892)
Introduction: The nineteenth century has been noted for two antagonistic tendencies; the one being toward greater freedom of individual action; the other toward vesting more power in government, consequently placing greater restrictions upon individual liberty. These opposing tendencies have been largely fostered by two schools of political thought equally extreme in their views. The Spencerian school holds that the State is a voluntary association of individuals for mutual protection, from which the person may withdraw at pleasure; that government is a necessary evil; and it looks with extreme jealousy on every act of government that is not an act of police. The socialistic school on the other hand holds that the government should not protect society against crime and foreign and domestic danger but also that it should oversee, control and even own the industries of the people regardless of individual rights. Happily, these tendencies have been neutralized by the conservative wisdom of statesmen and by the good sense of the people themselves, thus forming a middle ground of political belief.
Citation: Rice, Arthur Daniel. Government and liberty. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Government; Political philosophy; Liberty; Mill; Political science; Theses; Manuscripts (documents)